2019
DOI: 10.1093/heapol/czz128
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HIV treatment access, uptake and use among men who have sex with men in urban Indonesia: evidence from a qualitative study in three cities

Abstract: Men who have sex with men make up one of four key populations identified as critical to a successful HIV response in Indonesia. Despite international policies supporting HIV treatment in low- and middle-income countries, Indonesia is one of the few countries experiencing low coverage of HIV treatment and little decrease in HIV incidence. There is poor retention in care and low viral suppression rates among key populations such as men who have sex with men. The national government has committed to increasing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
3
20
1
1
Order By: Relevance
“…Consistent with global HIV guidelines that emphasise community involvement in national HIV responses, 42,43 our findings show that relations and practices involving female sex workers, community outreach workers, health workers and bosses enabled HIV testing among female sex workers in three urban settings in Indonesia. Our findings complement recent qualitative research around engagement with HIV care for testing and/or treatment among other key populations in Indonesia [35][36][37][38] which also illustrate how community mechanisms enhance engagement in HIV care. As such, our findings provide insight into the improvement of, and community participation and leadership in, HIV responses in Indonesia and other LMICs in the region.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with global HIV guidelines that emphasise community involvement in national HIV responses, 42,43 our findings show that relations and practices involving female sex workers, community outreach workers, health workers and bosses enabled HIV testing among female sex workers in three urban settings in Indonesia. Our findings complement recent qualitative research around engagement with HIV care for testing and/or treatment among other key populations in Indonesia [35][36][37][38] which also illustrate how community mechanisms enhance engagement in HIV care. As such, our findings provide insight into the improvement of, and community participation and leadership in, HIV responses in Indonesia and other LMICs in the region.…”
Section: Discussionsupporting
confidence: 79%
“…This qualitative study was part of a larger implementation research project designed to evaluate strategies to improve the HIV care cascade among female sex workers, people who inject drugs, transgender women and men who have sex with men in Indonesia. [35][36][37][38][39] Women were eligible to participate in the study if they were currently engaged in sex work, aged 16 years and able to provide informed consent. Participants were sampled purposively 40 to ensure diverse experiences with engagement in HIV testing, treatment and care services along the HIV care cascade.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings build on other research findings that document factors influencing access to HIV care among MSM, attending to the role that OWs play in Indonesia's HIV response. 10,15 It suggests the possibility not only for partnerships between healthcare workers and the community, but also for a crossover in personnel. It suggests that the MSM community is capable of participating in the Indonesian HIV response in more diverse capacities than only in the roles commonly associated with OWs.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, one qualitative study in three Indonesian cities found that social support from community-based OWs played an important role in helping MSM to navigate healthcare systems. 15 Another study found that, from the point of view of transgender women and MSM subjects of HIV prevention programs, OWs acted as a motivation for accessing HIV testing, care and treatment, along with the provision of easy-to-understand HIV information. The same study also described several possible limitations; including the perception that OWs could improve the appearance and delivery of HIV-related information so that it would be better tailored for specific groups within the community.…”
Section: Introductionmentioning
confidence: 99%
“…Studi HATI menunjukkan integrasi layanan tes dan pengobatan dalam satu atap meningkatkan peluang untuk memulai pengobatan secara lebih cepat dan keberhasilan pengobatan lebih baik (Januraga et al, 2018). Sebelumnya, penelitian kualitatif yang dilakukan oleh para peneliti sosial dan antropologi sebagai bagian awal dari HATI melaporkan hambatan akses ke pelayanan kesehatan meliputi aspek sosial dan kontekstual seperti persepsi terhadap sehat dan pengobatan, aspek kerahasiaan, dukungan dan pertimbangan stigma (Mitchell et al, 2019;Lazuardi et al, 2020). Di sinilah sekali lagi pendekatan multi-disiplin berhasil dimanfaatkan untuk mengidentifikasi masalah program kesehatan termasuk memformulasi intervensi yang sesuai untuk mengatasi hambatan sosial dan kontekstual yang ada untuk akses layanan HIV-AIDS.…”
Section: Menggunakan Inovasi Kedokteran Pencegahan Dalam Pendekatan Multi-disiplin Kesehatan Masyarakatunclassified